Areca-inspired core-shell structured MnO@C composite towards enhanced lithium-ion storage. (30th October 2021) - Zhu, Lingfeng; Wang, Yun; Wang, Minji; Xiong, Yaping; Zhang, Ze; Yu, Ji; Qu, Yaohui; Cai, Jianxin; Yang, Zhenyu
Abstract: MnO based composites are regarded as advanced conversion-type anode materials for lithium-ion batteries (LIBs) due to the low cost and high theoretical specific capacities (∼756 mA h g −1 ). Nevertheless, the undesirable structural stability and sluggish electrochemical reaction kinetics of the electrode materials lead to poor lithium storage performance. Herein, inspired by the structure of areca, the areca-like core-shell MnO@C composites containing of the MnO core and N-doped porous carbon shell are prepared via a biomass-assisted strategy. The formation mechanism of the MnO@C composites with well-defined core-shell structure are successfully clarified through heterogeneous contraction and carbon pyrolysis processes. As anodes for LIBs, the MnO@C composite delivers superior specific capacities of 915.9 and 218.1 mA h g −1 at 0.1 and 5.0 A g −1, respectively, and maintains outstanding cycling performance over 900 cycles at 1.0 A g −1 . More importantly, electrochemical kinetics tests further confirm that the improved LIBs capacity mainly originated from the unique areca-like core-shell structure and self-N doped porous carbon shell. Graphical abstract: Inspired by the structure of areca, unique areca-like core-shell structured MnO@C composites containing of the MnO core and N-doped porous carbon shell are prepared via a biomass-assisted strategy. As a result, the as-prepared MnO@C-800 composite presents remarkable electrochemical performance as LIBs anodes. Image 1 Highlights: Unique areca-like core-shell MnO@C composites are synthesized via a biomass-assisted strategy. An enhanced cycling performance of 314.3 mA h g −1 can be obtained over 900 cycles at high current density of 1.0 A g −1 . The remarkable Li + storage originates from the core-shell structural stability and fast electrochemical kinetics.